REGULATORY RISK MANAGEMENT STRATEGIES AND THE GROWTH OF MICROFINANCE SECTOR IN KENYA - Njuguna, Dr. James Rurigi; Gakure, Prof. Roselyn; Waititu, Dr. Anthony Gichuhi; Katuse, Dr. Paul (International Journal of Finance, 2017)
Purpose: The purpose of this study was to determine how the regulatory risk management strategies contribute to growth of MFI sector in Kenya Methodology: The study adopted a correlation survey research design. The population of this study was fifty seven (57) MFIs. The sampling frame was the list of MFIs provided in the AMFI website www.amfikenya.com. A sample of thirteen (17) MFIs was selected using the random sampling approach. A questionnaire and an interview schedule were the main data collection tools. Qualitative data was analyzed using content analysis whereas the quantitative data was analysed using Statistical Package for Social Sciences (SPSS) where descriptive and regression analysis were conducted to determine the relationship between enterprise risk management strategies and growth of MFIs. Findings: The study findings indicated that the MFI were compliant with all relevant regulations and that the regulatory environment provided an appropriate framework for the MFIs current and potential operations and legal status. The findings further indicated that the supervisory agency (CBK) provided adequate supervision of the MFI and the MFI has not in the past incurred heavy fines for violating regulations. Furthermore, the study findings indicated that the MFI has no cases pending in court over breach of contract. The regression results indicated that there was a positive effect on MFI growth Unique contribution to theory, practice and policy: it is recommended that the MFIs should continue practicing effective regulatory risk management practices such as development of appropriate regulatory framework for current and potential operations and legal status. This would significantly improve the growth of the MFI. The study also recommends that embracing supervision by the supervisory agency- CBK and honoring of contracts to avoid court cases and fines were good practices. It is recommended that compliance with all relevant regulations is crucial as it enhances the growth of MFIs. Study findings recommended that putting measures to prevent collection of illegal deposits and establishing a good working relationship with the regulatory authorities, will improve the growth of MFIs. The study recommends that encouraging open communication with regulators and provision of an opportunity to defuse any potential problems may be a crucial regulatory strategy as it improves the growth of MFIs